DTACC restricts bouton addition and regulates microtubule organization at the Drosophila neuromuscular junction. Issue 1 (21st November 2019) - Chou, Vivian T.; Johnson, Seth; Long, Jennifer; Vounatsos, Maxime; Van Vactor, David
Abstract: Regulation of the synaptic cytoskeleton is essential to proper neuronal development and wiring. Perturbations in neuronal microtubules (MTs) are associated with numerous pathologies, yet it remains unclear how changes in MTs may be coupled to synapse morphogenesis. Studies have identified many MT regulators that promote synapse growth. However, less is known about the factors that restrict growth, despite the potential links of synaptic overgrowth to severe neurological conditions. Here, we report that dTACC, which is implicated in MT assembly and stability, prevents synapse overgrowth at the Drosophila neuromuscular junction by restricting addition of new boutons throughout larval development. dTACC localizes to the axonal MT lattice and is required to maintain tubulin levels and the integrity of higher‐order MT structures in motor axon terminals. While previous reports have demonstrated the roles of MT‐stabilizing proteins in promoting synapse growth, our findings suggest that in certain contexts, MT stabilization may correlate with restricted growth.